Optimizing the User Experience: Identifying Opportunities to Improve Use of an Inpatient Portal - Walker, Daniel M.; Menser, Terri; Yen, Po-Yin; McAlearney, Ann Scheck (Applied Clinical Informatics, 2018)
Background Patient portals specifically designed for the inpatient setting have significant potential to improve patient care. However, little is known about how the users of this technology, the patients, may interact with the inpatient portals. As a result, hospitals have limited ability to design approaches that support patient use of the portal.Objectives This study aims to evaluate the user experience associated with an inpatient portal.Methods We used a Think-Aloud protocol to study user interactions with a commercially available inpatient portal—MyChart Bedside (MCB). Study participants included 19 English-speaking adults over the age of 18 years. In one-on-one sessions, participants narrated their experience using the MCB application and completing eight specific tasks. Recordings were transcribed and coded into three dimensions of the user experience: physical, cognitive, and sociobehavioral.Results Our analysis of the physical experience highlighted the navigational errors and technical challenges associated with the use of MCB. We also found that issues associated with the cognitive experience included comprehension problems that spurred anxiety and uncertainty. Analysis of the sociobehavioral experience suggested that users have different learning styles and preferences for learning including self-guided, handouts, and in-person training.Conclusion Inpatient portals may be an effective tool to improve the patient experience in the hospital. Moreover, making this technology available to inpatients may help to foster ongoing use of technology across the care continuum. However, deriving the benefits from the technology requires appropriate support. We identified multiple opportunities for hospital management to intervene. In particular, teaching patients to use the application by making a variety of instructional materials available could help to reduce several identified barriers to use. Additionally, hospitals should be prepared to manage patient anxiety and increased questioning arising from the availability of information in the inpatient portal application.
Keywords: user experience; patient portal; patient education; usability